Spatial distribution of patients with pressure injuries treated at a teaching hospital - Musse, Juliana de Oliveira; Braga, Cristina; Marreira, Marcelo; dos Reis, Maria José; Douradinho, Christian; Capeloa, Cristina Nunes; Menezes, João Carlos de Andrade; Ocon, Carlos Alberto; Isabella, Adriana Paula Jordão; Pitanga, Fernanda Sebastiana Mendes; Muniz, Claudia Cristina Soares; Filho, Alfredo Ribeiro; et al. (Seven Editora, 2024)
Introduction: Pressure injury (PF) is characterized by pressure exerted mainly on bony prominences, or even related to the use of medical devices. As epidemiological aspects are still scarce in the country, it is appropriate to produce studies that delimit the information for a better characterization of this public health problem, with extraterritorial dimensions. Geoprocessing is a revolutionary technology that encompasses the most diverse disciplines, data, equipment, analysis and interpretations from certain locations and geographic data, thus obtaining maps and/or spreadsheets with information relevant to that region that, when used in the health area, allows the identification and mapping of risks and injuries that affect the population. Objective: To demonstrate the technical experience of spatial demarcation and geoprocessing of patients with pressure injuries treated at a teaching hospital in the state of Sergipe. Method: A descriptive epidemiological study was carried out from a data sheet of patients with pressure injuries treated by the Skin Care Service team of a teaching hospital in Sergipe, between 2018 and 2022. Georeferencing and geoprocessing were developed in conjunction with Google Maps and Google Earth software. Results: The study sample consisted of 215 patients with pressure injuries (PF) in which the age group that stood out was the elderly (54.8%), followed by adults (40.0%). It is noted, in the spatial representation, that most of the patients with PL were residents of Greater Aracaju (n=130), followed by the East of Sergipe (n=23) and Central Agreste (n=18). Most of the LPs were acquired prior to admission to the institution studied (55.8%), while the others (44.2%) appeared during the hospital stay. Conclusion: In view of the analysis presented, it was possible to verify that most patients affected by PLs are men and elderly, and that the Greater Aracaju regional was the one that stood out the most because it concentrated most of the patients with PL, whether pre-existing or acquired at hospitalization. DOI:https://doi.org/10.56238/sevened2024.016-008